Using Assessment of Reading Test: Analysis Of Reading Comprehension Problems toward the Ninth Graders - Mahmudah, Khotimah (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
The difficulty to understand a text in English has become common problem for young learners who have English as Foreign Language. Through preliminary investigation, problems about reading comprehension were identified. Some students have gotten background knowledge about short functional text in form of descriptive and recount text in eight graders. This study examines reading comprehension problems about those types of text toward the ninth graders at SMP N 8 in Jambi City, Indonesia. This is a case study research. The purpose of this study is to explain the main English reading comprehension problem encountered by the ninth graders after doing reading test. Finding revealed problems from literal and interpretive comprehension level of reading based on the result of all students answer.